Sediment resuspension by wind, waves, and currents during meteorological frontal passages in a micro-tidal lagoon. (5th April 2016) - Carlin, Joseph A.; Lee, Guan-hong; Dellapenna, Timothy M.; Laverty, Paul
Abstract: Meteorological frontal passages are recognized as important mechanisms for remobilizing sediment in estuaries along the northern Gulf of Mexico, but few studies have addressed factors beyond wind speed as a predictor for resuspension. To better understand resuspension mechanisms during these events, this study investigated the effects of wind, waves, and currents on suspended sediment concentration near the seabed during frontal passages in the shallow, micro-tidal West Galveston Bay located along the Texas coast. In late January and early February 2013, two multi-day deployments of instrumented pods (an acoustic Doppler velocimeter, and an acoustic wave and current profiler) were conducted to capture two separate frontal passages. The results indicate that the bed shear stress under the combined effect of waves and currents showed a much stronger relationship to sediment resuspension (R 2  = 0.90) than wind stress alone (R 2  = 0.55), or currents alone (R 2  = 0.72). Increases in the bed shear stress due to the combined effects of waves and currents resulted from increased wave height, which is strongly related to fetch within the bay. Therefore, understanding fetch-limited wave heights as a function of wind speed and direction, in conjunction with basin geometry, may be a better way to predict sediment resuspension during meteorological frontal passages in the shallow bays of the northern Gulf of Mexico. Highlights: Measured waves, currents, and suspended sediment in a estuary during a cold front. Wave-current bed shear stress exhibited the strongest relationship to resuspension. Wave heights and thus resuspension are increased with increased fetch. Wave generation relative to fetch can better predict resuspension during the event.